Introduction: Confinement Beyond Site: Connecting Urban and Prison Ethnographies. Issue 1 (1st March 2020) - Weegels, Julienne; Jefferson, Andrew M.; Martin, Tomas Max
Abstract: Recognizing that the 'prison' and the 'street' are increasingly understood to be enmeshed sites of exclusion and confinement, this introduction proposes an analytical orientation towards relations and practices across these sites, which attends specifically to the ways in which they are mutually constitutive. Utilizing notions of traversal and porosity, we push debates on confinement beyond their prison-centric impulse. This decentring of the prison goes beyond reading one site in terms of the other (the street as just another carceral space; the prison as another site of exclusion). We challenge the divisiveness of prison/street binaries and the domination of boundary-making by emphasizing the importance of polyvalent experiences and by drawing attention to the practices of people who traverse the prison/street threshold. On the basis of the fine-grained ethnographic contributions making up this collection, the introduction points towards novel avenues for a (grounded) theorization of confinement in terms of overlap, traversal and porosity.